2019
DOI: 10.1213/ane.0000000000003807
|View full text |Cite
|
Sign up to set email alerts
|

Grade 3 Echocardiographic Diastolic Dysfunction Is Associated With Increased Risk of Major Adverse Cardiovascular Events After Surgery: A Retrospective Cohort Study

Abstract: BACKGROUND: Diastolic dysfunction is common and may increase the risk of cardiovascular complications. This study investigated the hypothesis that, in patients with isolated left ventricular diastolic dysfunction, higher grade diastolic dysfunction was associated with greater risk of major adverse cardiovascular events (MACEs) after surgery. METHODS: This was a retrospective cohort study. Data of adult patients with isolated echocardiographic diastolic dysfunction (ejection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…DD-related echocardiographic variables have been associated with postoperative MACE and mortality in noncardiac and nonhepatic surgery. [20][21][22][23][24][25] Of these variables, those relating to left ventricular filling pressure (septal e', lateral e', E/e' ratio) have all been implicated as the most important variables in this regard. [23,26,27,28] Impairments in these measurements have also been correlated with heart failure after LT, likely as sequela of structural abnormalities of the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…DD-related echocardiographic variables have been associated with postoperative MACE and mortality in noncardiac and nonhepatic surgery. [20][21][22][23][24][25] Of these variables, those relating to left ventricular filling pressure (septal e', lateral e', E/e' ratio) have all been implicated as the most important variables in this regard. [23,26,27,28] Impairments in these measurements have also been correlated with heart failure after LT, likely as sequela of structural abnormalities of the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…the association of diastolic dysfunction with post-operative adverse events, including pulmonary oedema, AF, and mortality. [134][135][136][137][138] A meta-analysis including 3876 patients undergoing NCS found preoperative diastolic dysfunction to be an independent risk factor for pulmonary oedema, congestive HF, and MI after surgery. 139 However, a recent retrospective study, including 7312 patients, showed no association between the degree of diastolic dysfunction and in-hospital mortality or hospital length of stay in NCS patients.…”
Section: Resting Transthoracic Echocardiographymentioning
confidence: 99%
“…The time needed for tissue Doppler measurements in the point-of-care context is within one minute, as shown in our previous study. [23] Diastolic dysfunction is initially often asymptomatic, but is still associated with an increased morbidity and all-cause mortality [2], adverse surgical outcome [4][5][6]27] and mortality in septic patients. [28,29] On the other side, in a recently published retrospective study on the prevalence of diastolic dysfunction and postoperative outcomes, no signi cant association was found between diastolic dysfunction and in-hospital mortality or acute kidney injury.…”
Section: Discussionmentioning
confidence: 99%